Population Growth and Primary School Enrollment in Yola-North, Adamawa-Nigeria (International Journal of Scientific Research and Management (IJSRM), 2018)
This work is centrally focused on population growth and how it affect the enrollment of school age children (6-11 years age group). The population of 2006 (199,674) was used as the base year to project the 2011 (234,329), 2016 (274,972) and 2021 (322,688) populations using the exponential growth model. Enrollment ratio was obtained by relating the total population of a particular level to the population that were enrolled at that particular level base on sex structure, the Gross Enrollment Ratio (GER) for male pupils from 2006 and 2011 was 70.21581% and 70.21696% which implies that 29.784% and 29.78304% of the male school age children are yet to be enrolled in schools, with a slight increase from 2006 to 2011. For 2016 and 2021, the GER is 70.2160% and 70.21696%, that is, 29.784% and 29.7822% of the male school age children will not be enrolled in schools with a slight increase from 2016 to 2021. The GER for female pupils from 2006 and 2011 was 74.03832% and 74.03432% which implies that 25.9618% and 25.96568% of the female school age children are yet to be enrolled in schools, 2016 to 2021 is 74.0347% and 74.0374% meaning that 25.96168% and 25.9626% of the female school age children will not be enrolled in schools by 2016 to 2021. The Sprague multipliers coefficient (SMC) table was applied to break down the five (5) years age group in to sex structures, in which the total age population at primary school (6-11) years as of 2006 base on sex structure was 14,689 and 13,258 for male and female respectively, for 2011 was 17,239 and 21,427 for male and female respectively. This paper has shown that, while the population of Yola-North LGA is rapidly growing, the enrollment of school age children is also increasing but very slowly.